Mother Bruce - Higgins, Ryan T. (Los Angeles ; New York : Disney*Hyperion, 2016)
Bruce is a grumpy bear who likes no one and nothing but cooked eggs, but when some eggs he was planning to boil hatch and the goslings believe he is their mother, he must try to make the best of the situation.
Keywords: Bears -- Fiction; Geese -- Fiction; Animals -- Infancy -- Fiction; Eggs -- Fiction